2019
DOI: 10.1001/jamainternmed.2019.1747
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnosis and Management of Primary Hyperparathyroidism Across the Veterans Affairs Health Care System

Abstract: IMPORTANCE Untreated primary hyperparathyroidism impairs quality of life and incurs substantial costs. Parathyroidectomy is a low-risk, high-success, definitive intervention.OBJECTIVES To determine the appropriateness of diagnostic evaluation for primary hyperparathyroidism in patients with hypercalcemia and the use of parathyroidectomy for the treatment of primary hyperparathyroidism across the Veterans Affairs (VA) health care system. DESIGN, SETTING, AND PARTICIPANTSA retrospective cohort study of veterans … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 41 publications
5
70
0
Order By: Relevance
“…Since surgical treatment remains the only treatment for severe/late‐stage PHPT, earlier detection of this condition may allow an opportunity for management of the disease through lifestyle changes and medical means. Some tertiary centers in the United States have published data suggesting large‐scale underdiagnosis of PHPT at their institutions 8‐10 . This research manuscript discusses trends in the diagnosis of PHPT at the University of Arkansas for Medical Sciences (UAMS).…”
Section: Introductionmentioning
confidence: 99%
“…Since surgical treatment remains the only treatment for severe/late‐stage PHPT, earlier detection of this condition may allow an opportunity for management of the disease through lifestyle changes and medical means. Some tertiary centers in the United States have published data suggesting large‐scale underdiagnosis of PHPT at their institutions 8‐10 . This research manuscript discusses trends in the diagnosis of PHPT at the University of Arkansas for Medical Sciences (UAMS).…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroidectomy (PTX) is the definitive treatment of PHPT for symptomatic patients [3]. Accumulating evidence show the benefits of PTX, including decreased progression of kidney disease and excellent long-term outcomes [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Parathyroidectomy (PTX) is the definitive treatment of PHPT for symptomatic patients [3]. Accumulating evidence show the benefits of PTX, including decreased progression of kidney disease and excellent long-term outcomes [3,4]. According to the current guidelines, PTX is suggested in all symptomatic patients [5], and it is suggested to be more cost-effective than observation or pharmacologic therapy, even when the patient is considered asymptomatic [6].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a simple means with which to diagnose primary hyperparathyroidism, for various reasons, this is a diagnosis that is often overlooked by lack of and/or incorrect interpretation of biochemical testing. [12][13][14][15][16][17] Multiple studies have shown that only approximately 30% of patients with documented hypercalcemia have ever had a PTH level assessed. [12][13][14][15][16][17] However, the frequency range at different facilities described in a single study varied widely from as low as 4% to as high as 57%.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Multiple studies have shown that only approximately 30% of patients with documented hypercalcemia have ever had a PTH level assessed. [12][13][14][15][16][17] However, the frequency range at different facilities described in a single study varied widely from as low as 4% to as high as 57%. 16 Hypercalcemia of malignancy (HCM) is an important complication of malignancy, most often seen in advanced stages of the clinical course of a patient.…”
Section: Introductionmentioning
confidence: 99%